Immunobiotic lactic acid bacteria beneficially regulate immune response triggered by poly(I:C) in porcine intestinal epithelial cells - Hosoya, Soichi (2011)
This study analyzed the functional expression of TLR3 in various gastrointestinal tissues from adult swine and shows that TLR3 is expressed preferentially in intestinal epithelial cells (IEC), CD172a +CD11R1 high and CD4 + cells from ileal Peyer's patches. We characterized the inflammatory immune response triggered by TLR3 activation in a clonal porcine intestinal epitheliocyte cell line (PIE cells) and in PIE-immune cell co-cultures, and demonstrated that these systems are valuable tools to study in vitro the immune response triggered by TLR3 on IEC and the interaction between IEC and immune cells. In addition, we selected an immunobiotic lactic acid bacteria strain, Lactobacillus casei MEP221106, able to beneficially regulate the anti-viral immune response triggered by poly(I:C) stimulation in PIE cells. Moreover, we deepened our understanding of the possible mechanisms of immunobiotic action by demonstrating that L. casei MEP221106 modulates the interaction between IEC and immune cells during the generation of a TLR3-mediated immune response.